Teaching Religion Within an Object-Oriented Ontology. Issue 1 (2nd January 2022) - MacKay, Michael Hubbard
Abstract: Religion is often taught as a topic within culture and scholars have increasingly argued alongside J. Z. Smith's position that religion cannot be taught as a thing-in-itself. This essay not only challenges that assumption, but it also addresses how religion can be taught and understood as a nonhuman entity outside of thought and in-itself. Within the developing literature about material religion, this essay will use Graham Harman's object-oriented ontology to theorize about learning how one might teach religion as an agentic thing-in-itself. Harman's unique speculative philosophy enables teaching to embrace material religion and things as agents, while creating a framework of assemblages and a social ontology to express the modern academic nature of "religion." This is an argument for teaching religion as religion, while emphasizing diversity, pluralism, and the nonhuman world of religion.